2021
DOI: 10.1002/andp.202100226
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Continuum Generation in Graphene‐Based Chalcogenide Slot Waveguide

Abstract: Slot waveguides comprised of Ge 23 Sb 7 S 70 and Si with and without graphene are considered for super-continuum generation in the mid-infrared range. The dispersion characteristics are optimized for the proposed waveguides comprised of Si and Ge 23 Sb 7 S 70 chalcogenide as the core and cladding, respectively with and without graphene sheets embedded in the proposed structure. The proposed waveguide without graphene possesses all-normal dispersion and the super-continuum spectra with bandwidth of 1.75 µm is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Gai et al and Shang et al [56][57][58] reported SC generation in Ge11.5As24Se64.5 waveguides pumped by the 1.55 µm laser With increasing pump power, the SC spectra broaden from 1 µm to 2 µm, as shown in Figure 12. GeSbS and GeSbSe were also used to prepare the waveguides since a heavy element Sb, in the glass can improve the optical nonlinearity [59][60][61][62][63][64]. Choi et al succeeded in fab ricating the GeSbS waveguide with a length of 15 mm and obtained SC spectra from 1.28 to 2.12 µm, as depicted in Figure 13, when the waveguide was pumped by 1.55 µm laser with peak power and a pulse width of 340 W and 500 fs, respectively.…”
Section: Chalcogenidementioning
confidence: 99%
See 1 more Smart Citation
“…Gai et al and Shang et al [56][57][58] reported SC generation in Ge11.5As24Se64.5 waveguides pumped by the 1.55 µm laser With increasing pump power, the SC spectra broaden from 1 µm to 2 µm, as shown in Figure 12. GeSbS and GeSbSe were also used to prepare the waveguides since a heavy element Sb, in the glass can improve the optical nonlinearity [59][60][61][62][63][64]. Choi et al succeeded in fab ricating the GeSbS waveguide with a length of 15 mm and obtained SC spectra from 1.28 to 2.12 µm, as depicted in Figure 13, when the waveguide was pumped by 1.55 µm laser with peak power and a pulse width of 340 W and 500 fs, respectively.…”
Section: Chalcogenidementioning
confidence: 99%
“…Choi et al succeeded in fab ricating the GeSbS waveguide with a length of 15 mm and obtained SC spectra from 1.28 to 2.12 µm, as depicted in Figure 13, when the waveguide was pumped by 1.55 µm laser with peak power and a pulse width of 340 W and 500 fs, respectively. GeSbS and GeSbSe were also used to prepare the waveguides since a heavy element, Sb, in the glass can improve the optical nonlinearity [59][60][61][62][63][64]. Choi et al succeeded in fabricating the GeSbS waveguide with a length of 15 mm and obtained SC spectra from 1.28 to 2.12 µm, as depicted in Figure 13, when the waveguide was pumped by 1.55 µm laser with peak power and a pulse width of 340 W and 500 fs, respectively.…”
Section: Chalcogenidementioning
confidence: 99%